2012
DOI: 10.5352/jls.2012.22.7.928
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of Ground Pork with Safflower Seed Powder as an Animal Fat Replacer

Abstract: This study was carried out to investigate the effect of the addition of safflower seed (Carthamus tinctorius L.) on the physicochemical properties of ground pork as an animal fat replacer. Three types of ground pork were evaluated: 20% pork fat added (control), 10% pork fat and 10% safflower seed powder added (10% SS), and 20% safflower seed powder added (20% SS). The moisture, protein, and ash contents were highest in 20% SS, and the fat content was highest in the control (p<0.05). The cooking yield, moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The Carthamus tinctorius L. seed has been used in traditional medicine in Asia including in Korea. It has also been used for osteoporosis and arthritis therapy in Korea [ 29 ]. Lignin, flavonoids, and serotonin derivatives have been isolated from Carthamus tinctorius L. seed [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Carthamus tinctorius L. seed has been used in traditional medicine in Asia including in Korea. It has also been used for osteoporosis and arthritis therapy in Korea [ 29 ]. Lignin, flavonoids, and serotonin derivatives have been isolated from Carthamus tinctorius L. seed [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Park et al (2012) reported that dry-cured meat was tend to oxidative rancidity by oxidants while curing. The result of TBARS against restructured jerky which was added the amount of treatments was showed in Table 3.…”
Section: Thiobarbituric Acid Reactive Substances (Tbars)mentioning
confidence: 99%
“…Starch has been recognized as a filler in surimi and used to increase the firmness of products and enhance the gel strength (Kim and Lee, 1987; VerrezBagnis et al, 1993; Wu et al, 1985). Lots of studies have performed to reduce fat content in meat products and fat replacements that possess the similar physicochemical properties with fat, safflower seed addition (Park et al, 2012), potato powder addition (Ali et al, 2011), and hazelnut or olive oil in fermented sausages (Kayaardi and Gok, 2004; Yildiz-Turp and Serdaroglu, 2008).…”
Section: Introductionmentioning
confidence: 99%